Photodegradation of Rhodamine-B Dye under Natural Sunlight using CdO - Dipali Lavate; Vikas Sawant; Ashok Khomane (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
The present study includes synthesis of CdO thin film by simple and cost effective chemical bath deposition method. Cadmium monochloroaceatate were used for preparation of CdO thin film.  The structural, optical properties of CdO thin film were investigated with the help of X-ray diffraction (XRD) and UV-Vis NIR double beam spectrometry. The XRD studies revealed that annealed thin film shows crystalline in nature having 48.4 nm in size. The optical band gap of thin film was found to be 2.13 eV. Scanning Electron Microscopy (SEM) images shows sphere like structure which is closely arranged with each other. The presence of functional group was confirmed by Fourier Transform Infra Red (FTIR). Brunauer–Emmett–Teller (BET) surface area analysis confirm formation of a mesoporous CdO with 6.01 m2/g surface area and 31.96 nm average pore diameter. The photocatalytic activity of prepared thin film was checked by using Rhodamine-B as a model dye under natural sunlight and found to be 48%. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).